How the capital structure affects business performance and value creation: a case study of a Brazilian slaughterhouse from 2008 to 2015 (Research, Society and Development, 2021)
The study aims to verify how the Capital Structure affects the Business Performance and Value Creation of a Brazilian company, in the meat and meat sector, operating globally, publicly traded and with its shares traded on the Stock Exchange Brazilian company B3, through Analysis of Financial Statements, in the period from 2008 to 2015. The research was carried out based on the data collected in Economática, deflation adjustments were made and later the main financial indexes and indicators of the company were calculated, with based on its Balance Sheet, Income Statement and Cash Flow. Horizontal Analysis, Vertical Analysis and the calculation of the indices were used: Liquidity, Profitability, Profitability, Indebtedness; being focused to understand how the Capital Structure affects Business Performance and Value Creation. The study allows to conclude that the inadequate form in the capital structure of the company in the period of analysis, carried out with a great debt in 2010 and 2011, only guarantees the company a good liquidity and capacity of payment in the short term; and fails to add economic value or business performance.